The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1111/ajps.12165
|View full text |Cite
|
Sign up to set email alerts
|

Everything to Everyone: The Electoral Consequences of the Broad‐Appeal Strategy in Europe

Abstract: Parties often tailor their campaign message differently to different groups of voters with the goal of appealing to a broader electorate with diverse preferences and thereby winning their votes. I argue that the strategy helps a party win votes if it can convince diverse groups of voters that the party is ideologically closer to their preferred positions. Using election data from nine Western European democracies, I first show that parties gain votes when they appeal broadly. Analysis of individual-level surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(154 citation statements)
references
References 57 publications
4
146
1
Order By: Relevance
“…In addition, we employ a recently proposed amendment that takes the share of the manifesto devoted to left-right issues as indicator for niche status (see Somer-Topcu 2015).…”
Section: Empir Ical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we employ a recently proposed amendment that takes the share of the manifesto devoted to left-right issues as indicator for niche status (see Somer-Topcu 2015).…”
Section: Empir Ical Resultsmentioning
confidence: 99%
“…We acknowledge that our measure has limitations as well. First, we cannot capture ambiguity in policy positions if a party decides to remain silent on the topic instead of issuing a position (for a discussion of various ambiguity strategies, see Milita, Ryan and Simas 2014;Somer-Topcu 2015). Although this might pose a serious problem if one were interested in a single issue, it is less relevant here as we measure positions and ambiguity at the aggregate level of a left-right ideological scale.…”
Section: Data and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…When electoral competition is high, for example, Abou‐Chadi and Orlowski () find that large mainstream parties will moderate their positions. Rovny (), moreover, has argued that parties may choose to blur issues they wish to de‐emphasise and Somer‐Topcu () has demonstrated that parties in multiparty systems that use a ‘broad appeal strategy’ do better electorally.…”
Section: Mainstream Party Convergence and Vote Switchingmentioning
confidence: 99%
“…In such a situation, parties may talk about issues associated with the secondary dimension, not to signal a clear position on these issues, but to deliberately blur their position on the secondary dimension. Blurring can be done in different ways, as according to Rovny it means adopting ''vague, contradictory or ambiguous positions'' instead of a clear ideological stance, with the aim of masking a party's ''spatial distance from voters in order to either attract broader support, or at least not deter voters on these issues'' (Rovny, 2013: 5-6; see also Somer-Topcu, 2014, andTomz andVan Houweling, 2009). A blurring strategy is outlined in Figure 2.…”
Section: Party Strategies In Two-dimensional Spacementioning
confidence: 99%